Handbook of High-End TVET (HETVET@UiTM) / Thuraiya Mohd, Noor Aileen Ibrahim, Ahmad Nazib Alias ... [et al.] - Mohd, Thuraiya; Ibrahim, Noor Aileen; Alias, Ahmad Nazib; Mohamed Zabidi, Zubainun; Md Nor, Zainuddin; Masrom, Suraya; Ahzahar, Nadira; Tahir, Azian; Abdul Rashid, Mohd Fadzil (Universiti Teknologi MARA, Perak, 2020)
This handbook serves as a guide and source of reference on the implementation of HETVET@UiTM. This handbook is not prescriptive or exclusive in nature but focusses on the practice of redesigning a curriculum, enhancing the teaching and learning (T & L) process and improving the present academic programme to become more demand-driven. Furthermore, this handbook fulfills the needs and objectives of UiTM and is the result of desk research (literature review), and also research on the current industry as well as the best practice of numerous countries which include Japan, Korea, Singapore, U.S, Vietnam, and Indonesia. In addition, the contents of this handbook include the introduction, definition, glossary, issues and challenges as well as the recommended implementation model of HETVET@UiTM.UiTM will continuously strive to become an institute of tertiary education that is aligned with the policy of implementing TVET whilst at the same time fulfilling one of the important objectives of the country which is developing the available human capital.